Ethnobotanical insights on the management of plant pests and diseases by smallholder farmers in Mpumalanga Province of South Africa - Kutullo N. Shai; Simeon A. Materechera; Stephen O. Amoo; Adeyemi O. Aremu (BMC, 2024)
Abstract Background Pests and diseases are a major contributor to yield losses in sub-Saharan Africa, prompting smallholder farmers to seek cost-effective, accessible and ecologically friendly alternatives for crop protection. This study explored the management of pests and diseases affecting crops across eight selected villages in Ehlanzeni District, Mpumalanga Province, South Africa. Methods A total of 120 smallholder farmers were purposefully selected utilising the snowball technique. Information on the management of plant pests and diseases was collected through interviews and focus group discussions using semi-structured interview schedules. Ethnobotanical indices, including relative frequency of citation (RFC), use-value (UV) and informant consensus factor (Fic), were used to quantify and rank the plants used for crop protection in the study area. Results Twenty-three plant species (16 naturalised exotics and seven indigenous plants) belonging to 16 families were used for managing pests (vertebrates and invertebrates) and diseases (fungal and bacterial related) affecting crops in the study area. The dominant (100%) crops cultivated by the participants were Allium cepa L., Mangifera indica L., Solanum lycopersicum L. and Zea mays L. The RFC value ranged from 0.08 to 0.83 and the three most popular plants for crop protection were Capsium annuum L. (0.83), A. cepa (0.63) and Dichrostachys cinerea (L.) Wight & Arn. (0.43). In terms of the UV, the five most promising plants used as biocontrol were Tulbaghia violacea (0.13), A. cepa (0.12), C. annuum L. (0.09), Solanum campylacanthum Hochst. Ex A.Rich.(0.09) and Pinus pinaster (0.08). Based on the Fic, four categories were established and dominated by fungal diseases (0.64). Furthermore, T. violacea and A. cepa were the most often mentioned plants used against fungal conditions. Other categories cited were bacterial diseases (0.3), invertebrate pests (0.11) and vertebrate pests (0.14), an indication that smallholder farmers had limited agreement or common knowledge about the plants used for their management. The preparation methods included maceration (38%), decoction (38%) and burning (24%). Foliar application (67%) and soil drenching (33%) were used for administering plant extracts during the management of crop pests and diseases. Conclusion The study highlights the importance of botanicals and associated indigenous knowledge among smallholder farmers in Mpumalanga Province, South Africa. It is pertinent to explore the valorisation of these botanicals by generating empirical data on their biological efficacies and phytochemical profiles.